ANALISIS TEKS EDITORIAL DAN OPINI PADA SURAT KABAR KOMPAS - Hasanah, Uswatun; Nisa, Khairun; Septiawan, Habi (Laboratorium Pembelajaran Bahasa, FKIP Universitas Lampung, 2024)
This study discusses the analysis of editorial and opinion texts in the Kompas online newspaper, namely kompas.com. This research is a descriptive qualitative research. The qualitative data is collected in the form of words from the text. The data sources used are editorial and opinion texts in the Kompas online newspaper. Analysis of the news structure is carried out based on two types of structure, namely the superstructure which includes the schematic and general structure of the news, the microstructure which includes 1) background; 2) use of words; 3) news expressions, and macro structures that include themes The results of this study are that the editorial text begins with a title that informs the death of a humanitarian hero, namely medical staff, while the opinion text begins with a title that informs how to respond to worry as a result of artificial intelligence technology. Elements of setting are found in opinion texts and editorial texts. The theme raised in the editorial text is humanity, while the theme in the Kompas.com opinion text is artificial intelligence. Penelitian ini membahas tentang analisis teks editorial dan opini pada surat kabar online Kompas, yaitu kompas.com. Penelitian ini adalah penelitian kualitatif deskriptif. Data kualitatifnya dikumpulkan dengan bentuk kata-kata dari teks. Sumber data yang digunakan ialah teks editorial dan opini pada surat kabar online kompas. Analisis struktur berita dilakukan berdasarkan dua jenis struktur, yaitu superstruktur yang mencakup skema dan struktur umum berita, struktur mikro yang mencakup 1) latar; 2) penggunaan kata; 3) ekspresi berita, dan struktur makro yang mencakup tema. Hasil penelitian ini adalah teks editorial dimulai dengan judul yang menginformasikan gugurnya pahlawan kemanusiaan yaitu tenaga medis, sedangkan teks opini dimulai dengan judul yang menginformasikan tentang bagaimana menyikapi rasa khawatir sebagai dampak dari teknologi kecerdasan buatan. Unsur dari latar ditemukan dalam teks opini dan teks editorial. Tema yang diangkat dalam teks editorial adalah rasa kemanusiaan, sedangkan tema pada teks opini kompas.com adalah kecerdasan buatan.